LEGO Group enterprise risk management - Læssøe, Hans (Henry Stewart Talks, 2012)
Proactive risk management, Strategic risk impact, Business continuity planning, Risk management standards, Enterprise risk management, Risk consolidation, Monte Carlo simulation, Risk appetite/risk tolerance, Risk map/heat map, ERM reporting, Project risk management, Project risk and opportunity management, Business system approach, Scenario planning, Strategic risk identification, Strategic risk prioritization, Financial simulation, Credit risk portfolio, Tornado diagrams